(untitled) (Tabanque. Revista Pedagógica, 2020)
Abstract: After years using an old-fashioned methodology at University and in Secondary School which, in our opinion, has downgraded student’s learning habits, a group of teachers from the two levels collaborate in a Pedagogical Innovation Project. The aim of the project is to consider whether using a proactive method and to receive previous training on it.